Ustalenie poziomu samodzielności decyzyjnej krajowych oddziałów przedsiębiorstw zagranicznych w Polsce w zakresie marketingu (określenie stanu i jego ocena) - raport z badań - Sobotkiewicz, Dariusz (Settlement of the level of decision independence of native departments of foreign enterprises in Poland in marketing scope (definition of the state and its estimation) - report of research, 2006)
The article presents the results of research, which are related to identification and estimation ofnthe level of decision independence of native departments of foreign enterprises in Poland innmarketing scope. The main focus is on the presentation of results of research refered to distribution, which are formulated in four spaces: marketing research, marketing planning, implementation of marketing plans and control in marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 303-321